Synergistic effects of biochar and potassium on enhancing methane production from carbohydrate-rich waste in mesophilic anaerobic digestion - Sugiarto, Yusron; Ahmad, Ary Mustofa; Maharsih, Inggit Kresna; Sunyoto, Nimas Mayang Sabrina; Setyawan, Hendrix Yulis; Rofiq, Muhamad Hafizhur; Zhu, Mingming (Springer, 2026)
This study investigates the synergistic effects of biochar and potassium additives on methane (CH4) production from carbohydrate-rich waste during two-phase anaerobic digestion. The research aims to determine the optimal concentrations of biochar and potassium that enhance CH4 yields from white bread waste. A factorial experimental design with 16 treatments, each replicated three times, was used to evaluate different concentrations of biochar (0, 5, 15, 25 g/L) and potassium (0, 1, 2, 3 g/L). Biogas production was measured daily using the volume displacement method, and the concentration of CH4 was analyzed to calculate both the cumulative CH4 yield and the daily CH4 production rate. Additionally, culture samples were collected for the analysis of the microbial community. Experimental results showed that the supplementation of biochar at a concentration of 5 g/L increased CH4 yield and CH4 production rate by 29% (from 3804.32 to 4915.78 mL/L) and 22% (from 507.24 to 616.92 mL/L/d) compared to control, respectively. Similarly, potassium supplementation at 3 g/L further boosted CH4 yield and CH4 production rate by 14% (from 4833.72 to 5510.04 mL/L) and 34% (from 586.81 to 785.94 mL/L/d) compared to the control. The combination of 5 g/L biochar and 3 g/L potassium yielded 5899.17 mL/L CH4, higher than that of adding the individual contribution from the biochar (4915.78 mL/L) and the potassium (5510.04 mL/L), indicating synergistic benefits. Microbial community analysis showed a 53.8% increase in Methanosaetaceae under the combined treatment, promoting more efficient CH4 generation pathways. This combination utilizes biochar’s ability to create a microhabitat for methanogenic microbes and potassium’s function as a metabolic cofactor. The novelty of this study lies in the synergistic use of biochar and potassium, which significantly accelerates CH4 production by enhancing microbial activity and stabilising the digestion process.
Keywords: Biochar; Methane optimisation; Microbial community; Potassium; Waste-to-energy; 31 Biological Sciences; 3106 Industrial biotechnology; 4004 Chemical engineering